Hardiness in the profession of sports coaches and physical education teachers - Ivanna Korobeinikova; Georgiy Korobeynikov; Oleg Kokun; Markus Raab; Lesia Korobeinikova; Iryna Syvash (IP Iermakov S.S., 2023)
Background and Study Aim. To study psychological features of sports coaches and physical education teachers' professional hardiness. Material and methods. The study involved 60 participants. Among them, 24 were coaches of children's and youth sports schools, 19 coaches of national teams of Ukraine and 17 physical education teachers. English-language version of the Professional Hardiness Questionnaire (PHQ) were used. The development of the English-language version of the PHQ was based on its initial Ukrainian-language version (http://prof-diagnost.org). The accuracy of its translation into English was checked and corrected by 12 bilingual specialists with degrees in medicine and/or psychology. To identify the peculiarities of the relationship between the indicators of professional resilience in different professional groups, we conducted a Spearman correlation analysis. Results. The analysis of professional hardiness revealed the presence of significant differences between the surveyed groups of coaches and physical education teachers by various indicators. It turned out that the length of service in the respective positions of national team coaches is significantly higher than that of Youth Sports School (YSS) coaches and physical education teachers. This indicates the presence of greater professional experience among this category of coaches. Accordingly, physical education teachers and coaches of national teams have significantly higher professional experience than coaches of YSS. As a result, the majority of young specialists are among the coaching staff of the YSS. The correlation coefficient between the general level of professional hardiness and the namely professional component of 0.80 is much higher for coaches of national teams. Among physical education teachers it reaches 0.61, most likely this is because the control over the work of this group is less specific in contrast to the work of the coach. Coaches of YSS have the lowest level of the namely professional component 0.50, we explain this by the fact that the overall level of experience in the position is half as much as in the previous two groups. Conclusions. The conducted analysis made it possible to establish relationships between the general level of professional hardiness and indicators of professional hardiness in each group of coaches and teachers.